Exploring the Role of Kiai in Fostering Supportive Relationships within Pesantren: A Case Study (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This research aims to formulate a Kiai helping service model in Serang City, Banten Province. This research uses a qualitative method with a case study approach. The research results show that Pesantren (Islamic boarding schools) and Kiai significantly strengthen spirituality and mentality regarding struggle, education, politics, economics, and helping services. Islamic boarding schools have been proven to pass on the legacy (noble values) taught by Kiai. These legacies include respect for ulama and science, good morals, and giving birth to new kiai by establishing Islamic boarding schools in their respective areas. Furthermore, community groups consult with the kiai regarding political, career, and business issues, spiritual guidance, the kiai's blessings, and household matters. Kiai's helping services are oriented towards two things, namely development and healing. In providing helping services, apart from advice, the Kiai also provides wiridan practices and prayer water. The practice of wiridan comes from the verses of the Al Qura'an and Asmaul Husna. Meanwhile, prayer water is used according to the Kiai's instructions. The helping models used are Sorogan, Bandongan, consultation, classical guidance, group guidance, and individual counseling. The use of each model is adjusted to the helpee's problem.